SAR Miniatures: Physical Scale Models as Immersive Prototypes for Spatially Augmented Environments - Omar Martinez Gasca; Lucas Van Dorpe; Ivo Dewit; Lukas Van Campenhout (Designs)
This paper explores the use of physical scale models as immersive prototypes in the design and development of Spatial Augmented Reality (SAR) environments. SAR integrates digital projections with physical spaces, offering benefits for spatial reasoning and coordinated activities. However, designing SAR systems at full scale presents challenges in testing and refinement due to their complex physical–digital properties. To address this, we developed augmented miniature environments for two case studies: an in-store retail navigation system and a manufacturing assembly process. These models effectively materialized SAR’s most important experiential qualities at a manageable scale, enabling the exploration of spatial relationships, coordinated user activity, and system functionality in a tangible and accessible way. The miniatures facilitated collaborative design, providing a shared medium for stakeholders to visualize and experiment with SAR applications. This paper presents augmented miniatures as effective tools for SAR design that foster creative exploration and communication, and highlights opportunities for future research in combining these models with digital prototyping technologies.